Intraoperative ultrasound guidance is associated with clear lumpectomy margins for breast cancer: a systematic review and meta-analysis. - Hong Pan; Naping Wu; Hao Ding; Qiang Ding; Juncheng Dai; Lijun Ling; Lin Chen; Xiaoming Zha; Xiaoan Liu; Wenbin Zhou; Shui Wang (PLoS ONE, 2013)
PURPOSE: Margin status is one of the most important predictors of local recurrence after breast conserving surgery (BCS). Intraoperative ultrasound guidance (IOUS) has the potential to improve surgical accuracy for breast cancer. The purpose of the present meta-analysis was to determine the efficacy of IOUS in breast cancer surgery and to compare the margin status to that of the more traditional Guide wire localization (GWL) or palpation-guidance. METHODS: We searched the database of PubMed for prospective and retrospective studies about the impact of IOUS on margin status of breast cancer, and a meta-analysis was conducted. RESULTS: Of the 13 studies included, 8 were eligible for the impact of IOUS on margin status of non-palpable breast cancers, 4 were eligible for palpable breast cancers, and 1 was for both non-palpable and palpable breast cancers. The rate of negative margins of breast cancers in IOUS group was significantly higher than that in control group without IOUS (risk ratio (RR)  = 1.37, 95% confidence interval (CI)  = 1.18-1.59 from 7 prospective studies, odds ratio (OR)  = 2.75, 95% CI  = 1.66-4.55 from 4 retrospective studies). For non-palpable breast cancers, IOUS-guidance enabled a significantly higher rate of negative margins than that of GWL-guidance (RR  = 1.26, 95% CI  = 1.09-1.46 from 6 prospective studies; OR  = 1.45, 95% CI  = 0.86-2.43 from 2 retrospective studies). For palpable breast cancers, relative to control group without IOUS, the RR for IOUS associated negative margins was 2.36 (95% CI  = 1.26-4.43) from 2 prospective studies, the OR was 2.71 (95% CI  = 1.25-5.87) from 2 retrospective studies. CONCLUSION: This study strongly suggests that IOUS is an accurate method for localization of non-palpable and palpable breast cancers. It is an efficient method of obtaining high proportion of negative margins and optimum resection volumes in patients undergoing BCS.